2006
DOI: 10.1016/j.ygeno.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

An anthropoid-specific segmental duplication on human chromosome 1q22

Abstract: Segmental duplications (SDs) play a key role in genome evolution by providing material for gene diversification and creation of variant or novel functions. They also mediate recombinations, resulting in microdeletions, which have occasionally been associated with human genetic diseases. Here, we present a detailed analysis of a large genomic region (about 240 kb), located on human chromosome 1q22, that contains a tandem SD, SD1q22. This duplication occurred about 37 million years ago in a lineage leading to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…30 Surprisingly, this segmental duplication does not exist in rat, mouse, chicken, or zebrafish, suggesting that this duplication may be associated with more recent evolutionary events specific for anthropoid primates. 30 It has been known that human chromosome 1q22, where the GON4L gene is located, is amplified in several human cancer types, including ovarian and breast cancer, 48 sarcomas, 49 and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…30 Surprisingly, this segmental duplication does not exist in rat, mouse, chicken, or zebrafish, suggesting that this duplication may be associated with more recent evolutionary events specific for anthropoid primates. 30 It has been known that human chromosome 1q22, where the GON4L gene is located, is amplified in several human cancer types, including ovarian and breast cancer, 48 sarcomas, 49 and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…30 Surprisingly, this segmental duplication does not exist in rat, mouse, chicken, or zebrafish, suggesting that this duplication may be associated with more recent evolutionary events specific for anthropoid primates. 30 It has been known that human chromosome 1q22, where the GON4L gene is located, is amplified in several human cancer types, including ovarian and breast cancer, 48 sarcomas, 49 and hepatocellular carcinoma. 50,51 A more detailed study has further confirmed that 3 loci covered by YAC955E11, YAC876B11, and YAC945D5 within 1q21-q22 have the highest amplified copy number in 5 of the 10 hepatocellular carcinoma cases examined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It would be worth exploring the usefulness of TSPYL2 for a serum marker of HCC. GON4L is a putative evolutionarily conserved transcription factor (49), but the functional significance of GON4L in cancer is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Blast searches in database revealed that the Udu protein had the highest homology to the human and mouse GON4L in both protein sequence and gene structure (Kuryshev et al, 2006;Liu et al, 2007). Caenorhabditis elegans gon-4, from which the name of the mammalian orthologue was derived, was identified as cell lineage regulator in gonadogenesis of Caenorhabditis elegans.…”
Section: Is Udu Coupled With Cell Cycle?mentioning
confidence: 99%